Respostas

2013-02-25T21:42:43-03:00

7x-35=8x-40

7x-8x=35-40

-x=-5 *(-1)

x=5

1 5 1
  • Usuário do Brainly
2013-02-25T23:28:42-03:00

Temos que:

 

7\cdot(\text{x}-5)=8\cdot(\text{x}-5)

 

Observe que:

 

7\cdot(\text{x}-5)=7\text{x}-35

 

8\cdot(\text{x}-5)=8\text{x}-40

 

Disso, deduzimos que:

 

7\text{x}-35=8\text{x}-40

 

Donde, segue:

 

8\text{x}-7\text{x}=40-35

 

\text{x}=5

 

Logo, chegamos à conclusão de que, \text{x}=5.

 

De fato, uma vez que:

 

7\cdot(5-5)=8\cdot(5-5)

 

7\cdot0=8\cdot0

1 5 1